Dietary phytochemicals as modulators of human pregnane X receptor - Zhang, Jie; Pavek, Petr; Kamaraj, Rajamanikkam; Ren, Li; Zhang, Tiehua (Critical reviews in food science and nutrition, 2023)
As a promiscuous xenobiotic sensor, pregnane X receptor (PXR) plays a crucial role in drug metabolism. Since dietary phytochemicals exhibit the potential to modulate human PXR, this review aims to summarize the plant-derived PXR modulators, including agonists, partial agonists, and antagonists. The crystal structures of the apo and ligand-bound forms of PXR especially that of PXR complexed with binary mixtures are summarized, in order to provide the structural basis for PXR binding promiscuity and synergistic activation of PXR by composite ligands. Furthermore, this review summarizes the characterized agonists, partial agonists, and antagonists of human PXR from botanical source. Contrary to PXR agonists, there are only a few antagonists obtained from botanical source due to the promiscuity of PXR. It is worth noting that trans-resveratrol and a series of methylindoles have been identified as partial agonists of PXR, both in activating PXR function, but also inhibiting the effect of other PXR agonists. Since antagonizing PXR function plays a crucial role in the prevention of drug-drug interactions and improvement of therapeutic efficacy, further research is necessary to screen more plant-derived PXR antagonists in the future. In summary, this review may contribute to understanding the roles of phytochemicals in food-drug and herb-drug interactions.
Keywords: antagonists; pregnanový X receptor; resveratrol; pregnane X receptor; Humans; fytonutrienty; lidé; Pregnane X Receptor; Phytochemicals; Agonists; Receptors, Steroid; dietary phytochemicals; Resveratrol; steroidní receptory